THE FIRST PERIOD OF ANTI-GOVERNMENT ACTIVITIES IN THE SHIDA KARTLI HIGHLANDS, GEORGIA - Guntsadze, Manuchar (PEOPLE: International Journal of Social Sciences, 2020)
Research of the conflict is very sensitive issue but very actual in Georgian case. The aim of this paper is to discuss some moments of problem connected to so called "South Ossetia". More specifically, its initial period. This conflict emerged at the period of the First Democratic Republic of Georgia in 1918-1921. During this time there were 3 facts of Anti-governmental activities from Ossetian Bolsheviks (in 1918, 1919 and 1920). Studying of this conflict is getting more popularity from 90-ies of 20th century when conflict renewed and Georgia gained independence from Soviet Union. After this time huge number of scientific articles and books were published concerning that conflicts.